Liguzinediol Enhances the Inotropic Effect of Rat Hearts via Inhibition of Protein Phosphatase (PP1 and PP2A) Activities. Issue 4 (April 2017) - Li, Sha; Huang, Huili; Zhang, Mengdan; Wang, Wei; Xue, Shuyin; Gao, Ying; Xie, Ming; Chen, Kesu; Liu, Fuming; Chen, Long
Abstract : Abstract: It has been demonstrated that liguzinediol (2, 5-dihydroxymethyl-3, 6-dimethylpyrazine, LZDO), a derivative of ligustrazine from Ligusticum wallichii Franch, exerts positive inotropy in isolated rat heart mediated by the sarcoplasmic reticulum Ca 2+ -ATPase (SERCA2a). Here, we further explore the underlying mechanism of the positive inotropic effect of LZDO in rat hearts. In vivo and ex vivo rat heart experiments, biochemistry, and Western blot techniques were used to analyze the rat heart contractility, and SERCA2a activity, phospholamban (PLB) phosphorylation, and protein phosphatase (PP1 and PP2A) activities in rat left ventricular myocytes, respectively. LZDO (20 mg/kg) significantly increased the inotropy of rat heart in vivo. In isolated rat heart experiments, LZDO (100 μM) restored the decreased inotropy induced by caffeine (0.5 mM); however, calyculin A (4 nM), an inhibitor of PP1 and PP2A, eliminated the inotropic effect of LZDO (100 μM). Moreover, LZDO (1, 10, and 100 μM) significantly enhanced SERCA2a activity and increased the levels of phosphorylated PLB on both serine-16 (Ser-16) and threonine-17 (Thr-17). In addition, LZDO (100 μM) significantly inhibited the activities of PP1 and PP2A. The positive inotropic effects of LZDO on in vivo and ex vivo rat hearts seem to be mediated through inhibition of PP1/PP2A, which may suppress dephosphorylated PLB and enhance SERCA2a activity. LZDO may prove effective in treating heart failure in clinical settings based on its unique biological mechanism.